In situ measurements of water uptake by black carbon‐containing aerosol in wildfire plumes. Issue 2 (20th January 2017) - Perring, Anne E.; Schwarz, Joshua P.; Markovic, Milos Z.; Fahey, David W.; Jimenez, Jose L.; Campuzano‐Jost, Pedro; Palm, Brett D.; Wisthaler, Armin; Mikoviny, Tomas; Diskin, Glenn; Sachse, Glen; Ziemba, Luke; et al.
Abstract: Water uptake by black carbon (BC)‐containing aerosol was quantified in North American wildfire plumes of varying age (1 to 40 h old) sampled during the SEAC 4 RS mission (2013). A Humidified Dual SP2 (HD‐SP2) is used to optically size BC‐containing particles under dry and humid conditions from which we extract the hygroscopicity parameter, κ, of materials internally mixed with BC. Instrumental variability and the uncertainty of the technique are briefly discussed. An ensemble average κ of 0.04 is found for the set of plumes sampled, consistent with previous estimates of bulk aerosol hygroscopicity from biomass burning sources. The temporal evolution of κ in the Yosemite Rim Fire plume is explored to constrain the rate of conversion of BC‐containing aerosol from hydrophobic to more hydrophilic modes in these emissions. A BC‐specific κ increase of 0.06 over 40 h is found, fit well with an exponential curve corresponding to a transition from a κ of 0 to a κ of 0.09 with an e ‐folding time of 29 h. Although only a few percent of wildfire particles contain BC, a similar κ increase is estimated for bulk aerosol and the measured aerosol composition is used to infer that the observed κ change is driven by a combination of incorporation of ammonium sulfate and oxidation of existing organic materials. Finally, a substantial fraction of wildfire‐generated BC‐containing aerosol is calculated to be active as cloud condensation nuclei shortly after emission likely indicating efficient wet removal. These results can constrain model treatment of BC from wildfire sources. Key Points: BC particles in wildfire plumes are found to be thickly coated with low hygroscopicity materials (ensemble average κ of 0.04) Hygroscopicity of BC‐containing particles increases in an evolving plume due to incorporation of ammonium sulfate and oxidation of organics A substantial fraction of wildfire‐generated BC‐containing aerosol is calculated to be CCN active shortly after emission